On the adsorption of Cu2+ and Zn2+ from wastewater using water hyacinth: the mathematical modelling approach - Eltahhan, Nashwa Tarek (My University, 2024)
Several industries utilize heavy metals in their industrial processes, eventually discharging them in their wastewater. Water contamination by heavy metals is a major environmental problem due to their acute toxicity and their accumulation in food chains. Therefore, intensive research has been carried out lately on the feasibility of water hyacinth as low cost adsorbent for the removal of heavy metals from wastewater. One of the present research objectives was to examine the potential of raw South African water hyacinth for the removal of Cu2+ and Zn2+ from a synthetic wastewater. The research work is divided into three core phases. In Phase I, batch equilibrium experiments were carried out to compare the performance of water hyacinth from the different countries, Egypt and South Africa, in the removal of copper and zinc from water solutions. The effect of several operating parameters on the uptake of Cu2+ and Zn2+ was tested. The tested parameters were the pH of the solution, contact time, water hyacinth dose and initial Cu2+ and Zn2+ concentration. The percent removal of Cu2+ and Zn2+ was found to increase with increasing the pH, contact time, and water hyacinth dose up to the point of equilibrium. However, it decreased with the increase in the initial concentration of Cu2+ and Zn2+. Langmuir and Freundlich isotherm models were used for the evaluation of the equilibrium experimental data. The correlation coefficients for Langmuir isotherm were 0.84 and 0.82 for copper and zinc adsorbed by Egyptian water hyacinth, respectively, and 0.98 for both copper and zinc adsorbed by South African water hyacinth. The correlation coefficients for Freundlich isotherm were 0.99 and 0.98 for copper and zinc adsorbed by Egyptian water hyacinth, respectively, and 0.94 and 0.98 for copper and zinc adsorbed by South African water hyacinth, respectively. Phase II was carried out to investigate the optimum operating conditions using Response Surface Methodology (RSM) design and General Algebraic Modeling System (GAMS). Here, optimization of an adsorption case study with conflicting optimal solutions based on singleobjective Response Surface Methodology (RSM) design was facilitated with the implementation of BARON solver based on General Algebraic Modeling System (GAMS) with identical variables, levels, and model equations. RSM suggested optimum settings of which the validation is quite expensive and onerous, whereas GAMS suggested a single optimum setting which makes it more economically viable, especially for large scale systems. Phase III was the final stage of the experimental part. It was conducted using fixed-bed column tests (continuous flow). The more promising water hyacinth which is the South African water hyacinth was used at that phase to define the impact of a number of parameters, namely the influent heavy metal concentration, bed depth, and the flowrate. The service time of the columns to breakthrough and to exhaustion was found to increase with the increase in the bed depth of the packed water hyacinth. However, it decreased with the increase in the initial Cu2+ and Zn2+ concentrations and the flowrate of the solution. Generic equations were used to describe the adsorption mechanism of the water hyacinth used to remove Cu2+ and Zn2+ from wastewater and validate the proposed generic model against experimental data. The results indicate the suitability of the generic models for copper and zinc removal using water hyacinth. The data obtained was used to scale up the adsorption column, and the economic feasibility was then demonstrated. Assuming 80% efficiency, the scale up column for copper can run for one day and requires 19.44 hr to treat 3.69 m3 of contaminated water using 22 kg of water hyacinth as adsorbent. On the other hand, the scale up column for zinc can run for one day and requires 19.44 hr to treat 3.44 m3 of contaminated water using 22 kg of water hyacinth as adsorbent. The production cost of the adsorption column was estimated at US$36,434.
A thesis submitted in partial fulfilment of the requirements for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2023
Keywords: Water hyacinth; Wastewater